The Recipient Vessel Hemodynamic Features Affect the Occurrence of Cerebral Edema in Moyamoya Disease After Surgical Revascularization: A Single-Center Retrospective Study - Xu, Liang; Li, Yin; Tong, Yun; Hu, Jun-wen; He, Xu-chao; Fu, Xiong-jie; Zhou, Guo-Yang; Cao, Yang; Yu, Xiao-bo; Zhou, Hang; Xu, Chao-ran; Wang, Lin (Frontiers in Neurology, 2022)
Objective: In moyamoya disease (MMD) with direct or combined revascularization, the initially hemodynamic recipient features are likely one of the main causes for acute hemodynamic disruption. Previous studies have explored the relationship between recipient diameter or flow velocity and postoperative complications, but there are still no optimal selection criteria with multiple potential recipient vessels. Cerebral edema is one of most common radiological manifestations in acute postoperative period. Here, this study assessed the hemodynamic characteristics of cortex vessels related with postoperative cerebral edema. Methods: All patients who had undergone direct or combined revascularization with preoperative DSA between 2019 and 2021 were eligible for inclusion in this study. The application of DSA was performed and regular radiological examinations were employed after surgery. DSA was analyzed with the hemodynamic features within chosen recipient vessels. Cerebral edema was identified as low density image on CT or high signaling on MRI T2 phase. The recipient hemodynamic characteristics and demographic presentation, as well as clinical data, were retrospectively analyzed in this study. Results: 103 patients underwent direct or combined revascularization with preoperative DSA. The mean age of this enrolled cohort was 44.31 ± 10.386 years, in which bilateral involved MMD accounted for the main part. The preliminary correlation analysis found preoperative disease period (p= 0.078), recipients observed in angiography (p= 0.002) and surgery on the left (p= 0.097) may be associated with cerebral edema. The following regression analysis confirmed low occurrence of cerebral edema was accompanied with recipients observed in angiography (p= 0.003). After subdivide by flow direction and hemodynamic sources, the incidence rate of anterograde direction, anterior sources and posterior sources were significantly lower than undetected recipients. Conclusions: Cerebral edema is a common radiological manifestation in MMDs after surgery. In this study, the observation in angiography reliably identify a variety of physiological or pathological recipient detection, flow direction and hemodynamic sources in MMD patients after revascularization, which indicates the selection strategy of potential recipients and highlights the importance of recipient observability in DSA. Meanwhile, vascular conditions determinated by recipient hemodynamics meditate the occurrence of postoperative cerebral edema.